2003
DOI: 10.1016/s1010-7940(03)00454-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial colonization of the donor lower airways is a predictor of poor outcome in lung transplantation☆

Abstract: Donor lungs with lower airways colonized with bacteria result in inferior recipient outcome. Bacterial colonization of the donor lower airways could therefore be used as a marker of donor lung injury, but evidence from a prospective study is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 15 publications
4
46
1
2
Order By: Relevance
“…Other studies have demonstrated that donor colonization impairs LTx outcomes [30], with the impact of donor-to-host transmission being previously described [31]. In our study, airway colonization was evident in the bronchoalveolar lavage fluid of 50% of EVLR patients after LTx, much higher than would be expected or indeed observed among non-ELVR patients.…”
Section: Discussionsupporting
confidence: 61%
“…Other studies have demonstrated that donor colonization impairs LTx outcomes [30], with the impact of donor-to-host transmission being previously described [31]. In our study, airway colonization was evident in the bronchoalveolar lavage fluid of 50% of EVLR patients after LTx, much higher than would be expected or indeed observed among non-ELVR patients.…”
Section: Discussionsupporting
confidence: 61%
“…Although dendritic cells are the most potent APCs, the lung is rich in monocytes/macrophages and depletion of these cells in the donor lung before transplantation was associated with decreased local induction of proinflammatory cytokines, such as TNF-a (44). The donor lung is frequently colonized with microbial pathogens that are a rich source of TLR ligands (45), and lung transplantation itself results in exposure of antigenic col(V) (10). We hypothesize that the combination of donor lung monocyte/macrophage-induced alloimmunity that is enhanced by TLR ligands may result in high local levels of proinflammatory cytokines, such as IL-1 and IL-6, which may potentiate PGD in col(V)-presensitized patients, while promoting de novo development of Th-17 cells reactive to col(V) in patients not previously col(V) reactive, thus predisposing to BOS (14).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that 46-89% of donor lungs had positive bronchoalveolar lavage (BAL) bacterial cultures and that frequent donor-to-recipient transmission of infection put the recipients at higher risk for subsequent lung infection and poor posttransplant outcome (3)(4)(5). Bacteria cause most cases of VAP, and many infections are polymicrobial.…”
Section: Introductionmentioning
confidence: 99%